Encyclopedia: Nature-Based Learning Initiative to Enhance Students' Critical Thinking - Audrey Louise Makatita; Jeany Tomatatala; Mayesti Rambu Jati; Mia Fransiska mangi Dimu (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to implement a Nature-Based Learning Initiative as an innovative solution to enhance students' critical thinking skills at SD Inpres Hiliwuku, East Sumba. The school faces significant challenges due to its remote location and a lack of electricity and internet access, which restricts conventional teaching methods. This approach utilizes the surrounding natural environment as a "living laboratory" and primary learning resource, supported by the use of a printed Nature-Based Encyclopedia as a physical reference for students to verify field findings. Data analysis results indicate a significant improvement in critical thinking abilities, where the average pre-test score of 49.75 (Insufficient category) increased drastically to 80.25 (Good category) in the post-test. All students showed improvement, with 70% reaching the "Good" to "Very Good" categories. In conclusion, nature-based learning supported by contextual encyclopedias is an effective, low-cost, and sustainable educational alternative that optimizes local potential to overcome infrastructure limitations in remote areas.